(untitled) (Journal of Information Technologies in Education (ITE), 2015)
Redefining of modern information and communication technologies (ICT) from teaching aids to teaching process subjects, continuous growth of their subjectivity necessary demands appropriate knowledge, skills, appropriate attitude to didactic capabilities of ICT, ability to cooperate with them and to build pupils learning activity aimed at formation and development of self organization, self development skills, promoting their subjective position in getting education that will be readiness of modern teacher to organize effective professional activities in polysubjective learning environment (PLE). The new tasks of humanitarian teacher related to self selection and design of educational content as well as the modeling of the learning process in conditions of PLE virtualized alternatives choice, impose special requirements to professionally important teacher’s personality qualities, rather to his readiness to implement effective professional work in such conditions. In this article the essence of future humanitarian teacher readiness concept to professional activity in polysubjective educational environment is proved. The structure of the readiness is analyzed. Psychological strategy of cooperation, reflective, motivational and informational partials are substantiated and characterized as components of the future humanitarian teacher readiness to professional activities in polysubjective educational environment.